Wpływ autorytetu (umundurowania) na posłuszeństwo w zakresie przestrzegania przez pieszych przepisów o ruchu drogowym = The influence of authority (uniforms) on obedience to respect pedestrian traffic regulations - Góralewska-Słońska, Anna Maria; Kuchar-Pietrzak, Małgorzata; Siwczyk-Kępa, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The goal of this article was to check whether the Pole is obedient to authority (which is a represented by a police uniform)? Is uniform exposure sufficient factor, which convinces respondents to behave in line with the law on road traffic safety? The authority has been identified with a police uniform, because the right to wear the uniform under the threat of criminal sanctions have only policemen. Because of the professional role they have the right to enforce obedience from individuals or groups representing civil society.
Keywords: autorytet; posłuszeństwo; uprawomocniony uniform - mundur policyjny; authority; obedience; validated uniform - a police uniform